Emotional intelligence profile of tourists and its impact on tourism - Borges, Ana Pinto (2021)
The study aims to characterize, for the first time, the emotional intelligence profile of the tourists visiting the city of Porto as well as to observe its influence on the intention to return and activities perfomed during the stay, along with other sociodemographic factors,To achieve these purposes, we used a sample of 886 responses with the following purposes: on the one hand, to get the emotional intelligence constructs by applying the confirmatory factorial analysis, and on the other hand, to apply a logit model to describe the intention to return. Four constructs of tourists’ emotional intelligence emerged: emotion regulation, emotion use, evaluation of their own emotions, and evaluation of others’ emotions. . The first construct was indicated as the most important leading us to conclude that tourists have the ability to control their own emotions, presenting a strong emotional control. The four constructs and different variables of the tourists’ socio-demographic profile show a positive effect on the intention to return. This type of information is highly useful for the sector since it allows the definition of communication strategies and guides businesses to adapt to the profile of tourists.